Research on Calculation Method of Gear Tooth Thermal Deformation Based on the Equivalent Gear Method - Gao Xuepeng; Jiang Qinchen; Xiao Yang; Zhang Quanqing; Qiao Zheye (Jixie chuandong)
Based on the calculation method of thermal deformation of spur gears, a calculation and analysis model of thermal deformation with equivalent spur gears as the object is formed. According to the difference between different types of gears and equivalent spur gears, the calculation methods of thermal deformation of helical cylindrical gears and straight bevel gears are deduced. The proposed methods are compared and verified by finite element simulation. Finally, the method is extended to the calculation of thermal deformation of spiral bevel gears. The results show that the thermal deformation of the tooth surface calculated by the proposed method is in good agreement with the finite element simulation results, which can truly reflect the deformation degree of the tooth surface after heating. The numerical difference at the maximum thermal deformation is less than 8%. This method provides a new idea for the calculation of thermal deformation of gears with complex tooth surfaces.